(3GdefGXQ hGdeQGjG GdeMQbIs - (3CMeO Hf YjSis
(3ChdgG (B:s
(3Gdbhd ai GdHUQ hEOQGcg (B: (3bGdJ GdChGFd (B: (3Ef GdHUQ gh CYXe GdMhGS bOQkG hCLdgG abOkG hCcKQgG YedkG s
(3BNQgG (B:s
(3ef NQhL GdCdhGf GdKdGKI (B: (3GdTeSjI hGdHUQjI hGdfGQjI hGJUGdgG hGfYcGSgG HYhf Gddg JYGdi s
(3ehVMg HGdCTcGd GdgfOSjIs
(3hYdi UaMI GdYfhGf JhbjY GdYdGeI eMeO Hf GHQGgje Hf SGYO GdCfUGQi GdeYQha HGHf GdCcaGfi GdeJhai SfI (B749s
(3Cdag Ydi ePgH CbdjOS ai Ydd GdHUQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B210 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs